Cu(II) Doped TiO2 for Photodegradation of Remazol Black B in Aqueous Solution - Momen, Md Abdul; Rahman, Md Ataur; Begum, Hosne Ara; Hossain, Md Mufazzal (Dhaka University Journal of Science, 2022)
In the present investigation, Cu(II) doped TiO2 was prepared by a precipitation method. The precipitate was calcined at 300 ºC for 2 hours. The prepared doped catalyst was characterized by scanning electron microscope (SEM), energy dispersive X-ray (EDX) spectroscopy and X-ray diffractometry (XRD). SEM images revealed that the morphology of the doped catalyst was different from that of TiO2. Elemental analysis was accomplished by EDX that indicated the presence of Cu, Ti and O atoms in the prepared sample. XRD analysis confirmed that TiO2 was present as anatase with almost no distortion in peak position due to the presence of Cu(II) in some interstitial sites. Photodegradation of remazol black B (RBB) was carried out at different experimental conditions under different light sources. The catalytic efficiency of Cu(II) doped TiO2 increased up to a certain dosage then reduced with a further increase in the amount of photocatalyst. The optimum conditions for degradation was found at pH 3.0 under UV light. Under these experimental conditions, Cu(II) doped TiO2 degraded 98.8% of RBB, on the other hand, undoped TiO2 degraded only 80.0% of RBB. Dhaka Univ. J. Sci. 70(1): 64-69, 2022 (January)